Succession of Traditions in the Kazakh Literature - Ф.Т., Жумaжaновa (Journal of Oriental Studies, 2019)
This articleconsidersone of the most difficultand insufficiently studied problems in diachronic and theoretical aspects the succession of traditions in the Kazakh literature. As the main source of the succession of traditions in Kazakh literature isthe piecesof work from the ancient literature, for us the study of them is important. Nowadaysthey are becoming the research object of national literature studies. The issue of sharia was considered and covered not only in the works of Abay, but also in the works of earlyother Kazakh poets like Bukhar Zhyrau Kalkamanuly, Dulat Babatayuly, Zhusip Khoja, and Mailykhoja Sultankhojauly. Who or what contributed to the coverage of this issue in the writings of poets remains interesting and relevant, and the answer, as we know from the history of literature, is in the works of that period, which became the object of our research. Key words: Succession of traditions, Sharia, ancient literature, literary heritage, masterpiece, Sufi literature.